Review of Impact and Handling of Potential Antihypertensive Drug Interactions in Chronic Kidney Disease Patients: Review Dampak dan Penanganan Potensi Interaksi Obat Golongan Antihipertensi pada Pasien Penyakit Ginjal Kronis - Ni Made Susilawati; Eli Halimah; Siti Saidah (Universitas Tadulako, 2021)
Drug interaction is a type of Drug-Related Problems (DRPs) that caneventually increase morbidity and mortality rates. CKD patients have asignificant risk of developing polypharmacy due to comorbid diseases andpharmacokinetics' alteration. The literature review was conducted byexploring all of the articles related to the drug interaction using druginteraction analysis program in CKD patients, which obtained from threedatabases, namely Google Scholar, PubMed, and Science Direct, usingseveral keywords combination. Based on the comprehensive reviewsconducted, it is known that the most common effects of antihypertensivedrug interactions in CKD patients are decreasing effects of antihypertensivedrugs, hypotension, and hyperkalemia. Handling management used for theemergence of potential drug interactions is based on the severity of the druginteractions and complete knowledge of the patients' clinical condition. Themanagement of drug interaction by monitoring blood pressure, diuresis, andpotassium levels; Monitor the related effect symptoms; Monitor the fluidand body weight; Monitor the kidney and heart function. On the conditionwhere the handling management of potential drug interactions is not carriedout, elevated morbidity and mortality rates are the risks of complicationsarising from the drug interactions.